(untitled) (Faridpur Medical College Journal, 2018)
Mechanical bowel preparation is routinely done before colorectal surgeries to reduce morbidity and mortality all over the world. The role of mechanical bowel preparation in preventing complications is recently disputed. The aim of the study was to assess whether elective colorectal surgery can be performed without mechanical bowel preparation. This cross sectional comparative study was carried out to assess the role of mechanical bowel preparation in post-operative complications in elective colon and rectal surgery in the department of surgery of Bangabandhu Sheikh Mujib Medical University, Dhaka Medical College Hospital and SSMC-Mitford Hospital during the period of 1st January 2007 to 31st December 2007. Fifty patients undergoing surgery for carcinoma of colon and rectum were included in the study. Patients were allocated in two groups by non-probability convenient consecutive technique-one group with mechanical bowel preparation with polyethylene glycol and one group with no preparation before surgery. All patients in the study group were followed up for at least one month after surgery for wound infection, anastomotic leakage and intra-abdominal infection. Total 50 patients were randomly divided into two groups (group A, 25 patients & Group B, 25 patients). Group A was the preparatory group and Group B was the non-preparatory group. The type of surgical procedure and the type of anastomosis did not differ significantly between two groups. Sixty percent patients of group A developed post-operative complications; on the other hand 40% patients of group B developed post-operative complications. My study proved that no advantage is gained by pre-operative mechanical bowel preparation and can be easily avoided in order to save the patient from unwanted events like nausea, vomiting, electrolyte imbalance and also increased chance of post-operative complication. Faridpur Med. Coll. J. Jan 2018;13(1): 8-11